Estimation of height from percutaneous length of fibula in adult Bengalee population - Dilip Kumar Mondal; Panchali Datta; Rajarshi Roy (Al Ameen Medical College, 2023)
Background: Morphology and morphometry of lengths of bones with respect of the height of the person vary from country to country and from place to place. Objective: objective was to study relationship between the percutaneous length of fibula & height of that individual in adult bengalee population. Methods: In a cross sectional descriptive study, 400 (200male & 200 female) adult bengalee person were studied and the percutaneous length of fibula & their height were measured and analysed. Results: Positive correlation was found between the height of the person and the length of both right and left fibula separately both in case of male and female subjects. Also correlation between the right and left fibula was statistically significant both in male and female subjects. Conclusion: In the present study the results showed that length of fibula is important for estimating height in respect of specific racial, geographical and gender specific population group (here adult Bengalee population). Separate and independent linear regression equation derived for the specific population group & it demonstrates that the length of fibula (long bone) can be used to estimate the stature of adult Bengalee population in Burdwan District.